COVID-19 Vaccine Hesitancy by Smoking Status Among Ohio Adults - Prashant Bhandari; Andreas A. Teferra; Michael Nau; Leyla Tosun; Timothy R. Sahr; Naomi Freedner; Amy K. Ferketich (Ohio Journal of Public Health, 2024)
Background: Research in other countries and limited findings in the United States suggest that adults who smoke are less likely to get COVID-19 vaccines. The objective of this study was to examine vaccine hesitancy by smoking status in Ohio. Methods: We performed a secondary analysis of multiple 8-week waves of the Ohio COVID-19 Survey (OCS) from March 2021 to July 2022. The OCS participants comprised a subsample from the 2019 Ohio Medicaid Assessment Survey, a statewide health survey. After the COVID-19 vaccine was available, participants were asked about vaccination status and, among those not vaccinated, vaccine intentions. To compare vaccine hesitancy by smoking status, multivariable survey-weighted logistic regression models were fit, adjusted for potential confounders. Reason for vaccine hesitancy was asked using an open-ended question; data were coded and analyzed descriptively. Results: Adults who smoked, compared to those who never smoked, had significantly higher odds of being vaccine hesitant between March and April 2021, June and August 2021, October and November 2021, and May and July 2022, with odds ratios ranging from 1.60 to 2.44. Reasons for vaccine hesitancy were not different by smoking status. Conclusion: Although the difference in hesitancy by smoking status was attenuated after December 2021, coincid-ing with an increase in cases, evidence from summer 2022 indicates that adults who smoked continued to display vaccine hesitancy. These results have implications for COVID-19-related outcomes and more research is needed to understand reasons for vaccine hesitancy, which could also serve to educate adults who smoke about vaccination for other diseases.
Keywords: COVID-19; Vaccine hesitancy; Smoking; Survey research